Zinc supplementation estrategies for adults (Research, Society and Development, 2020)
Zinc is a multifunctional element, essential for all physiological processes, acting as a catalyst, structural and regulatory element. Mineral deficiency is associated with severe pathological conditions that mostly arise due to dietary deficiency, the presence of chelating compounds in food, disturbances in the gastrointestinal absorption process or elevated urinary levels. Zinc has long been used as a therapeutic agent in the adjunctive treatment of various diseases. Zinc supplementation demonstrated beneficial effects, in situations of diets poor in animal products or rich in phytates and even in hypozincemic individuals. The aim of the study was to conduct a systematic review of zinc supplementation strategies in adults over the past ten years. The data were obtained through a systematic review of the literature that was developed by searching for articles in the Pub Med, Science Direct and Scielo databases by two researchers independently. 25 articles were included in the review. The most used form of supplementation was zinc sulfate (60% of the studies) and zinc gluconate in 24% of the surveys. The daily dosage varied between 12 mg and 150 mg of elemental zinc, with duration varying from four days to eighteen months. Zinc is essential for human health and its use as a supplement has been frequent for healthy individuals and in auxiliary therapy and prevention of many diseases, with zinc sulfate and gluconate as the main forms of supplement.